2009
DOI: 10.3181/0812-rm-354
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Action of Kai Xin San Aqueous Extract on Depressive-Like Symptoms and Cognition Deficit Induced by Chronic Mild Stress

Abstract: Kai Xin San (KXS), a traditional Chinese herbal medicine, has been used clinically for the treatment of depressive disorders and cognitive impairment for centuries. However, the effects of KXS on cognitive dysfunction induced by depression have not been evaluated scientifically. The present study aimed to explore the antidepressant-like and nootropic effects of an aqueous extract of KXS (at doses of 0.3, 0.9, and 2.7 g/kg/day) using chronic mild stress (CMS) as a model of depression. Depressive symptoms were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
74
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(77 citation statements)
references
References 43 publications
3
74
0
Order By: Relevance
“…The herbal preparation in the form of powder is used only when the patient has to take the drug for a prolonged period of time. In the extraction of KXS, water was selected as the solvent for two reasons: (i) water is the common solvent in TCM preparation and frequently used for the KXS preparation, and (ii) the water extract of KXS was reported to exert anti-depressant-like effects on the chronic mild stress animal model [7]. The extracts were dried and stored at À201C.…”
Section: Optimization Of Extraction Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The herbal preparation in the form of powder is used only when the patient has to take the drug for a prolonged period of time. In the extraction of KXS, water was selected as the solvent for two reasons: (i) water is the common solvent in TCM preparation and frequently used for the KXS preparation, and (ii) the water extract of KXS was reported to exert anti-depressant-like effects on the chronic mild stress animal model [7]. The extracts were dried and stored at À201C.…”
Section: Optimization Of Extraction Conditionsmentioning
confidence: 99%
“…Indeed, KXS has been reported to enhance the memory [6] and to relieve the symptoms of depressive disorder, as revealed in animal studies [7]. The first description of KXS is in Beiji Qianjin Yaofang oThousand Formulae for Emergency4 written by Sun Si-miao of Tang Dynasty in 652 A.D.…”
Section: Introductionmentioning
confidence: 99%
“…It eventually damages the ability to implement simplest tasks [1][2][3][4]. AD has been officially listed as the fifth-leading cause of death for individuals age 65 and older.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, previous studies have also demonstrated that KXS ameliorates learning and memory deficit in amygdala-lesioned and thymectomy-, ethanol- and scopolamine-induced injury in mice, even in senescence-accelerated mice, by the step-down or MWM test [13,18,20]. Further studies demonstrated that part of the KXS mechanism is antidepressant-like by modulating the HPA axis and the monoamine neurotransmitters [30] and increasing the levels of phosphorylated CREB in CA1, CA3 and DG in the hippocampus of rats suffering from chronic stress [29]. The effects of stress on body weight are still controversial.…”
Section: Discussionmentioning
confidence: 99%